(untitled) (Materiali di Estetica. Terza serie, 2023)
Through an interdisciplinary perspective, the article aims to investigate the notion of “vision”. The argument begins by developing an aesthetic of the invisible, of the darkness which hampers the sight and the black color beside it. As darkness is the mythical primordial state of the universe, the performing scene enveloped in darkness seems the embryonic condition of an incoming world of colors. When darkness begins to disappear, shading (or chiaroscuro) enters the scene. It’s the infra-vision environment, where shades of grey occur: it establishes itself as the liminal area in which the eye begins to catch a glimpse of the chromatic possibilities of images. Straddling visual and performing arts, the article analyzes some significant instances of the “thinking through light” that belongs to artists such as Turrell, Eliasson, Teshigawara and Takatani (Chroma, 2012). In recent years, these artists have questioned the perception of the audience by using darkness, shading, light and color.